Il diritto di resistenza nel Settecento italiano - Stefania Stoffella (Laboratoire Italien)
The Italian translation of the De iure naturae et gentium by Pufendorf (1672) –translation that allowed the natural law theory, developed in Germany, to become widespread in Italy in the middle of the 18th century– is a very important event in European political and juridical culture. The diffusion of Pufendorf’s thought was made possible thanks to the “French channel”: the Italian translator, Giovambattista Almici (1717-1793) followed the French translation of Jean Barbeyrac (1674-1744) –a complete re-elaboration of the original text– to which he added his own corrections. In this story, Clemente Baroni Cavalcabò (1726-1796) and Giovanni Chiaramonti (1731-1796) play a major part. The unpublished correspondence between Baroni, attracted by Montesquieu’s thought, and Chiaramonti bears direct testimony to the first Italian reception of the political theory derived from the works of Grotius and Pufendorf. In the letters here published, Baroni justifies the right of resistance on the basis of natural principles. Those documents thus offer new elements helping understand to what extent and with what consequences the Italian political class participated in the first circulation of the modern theory of natural law. In this regard, they also contribute to the study of a historical debate that is still open today.